Effect of Partial Replacement of Manufactured Sand Produced from Stone Crushing by Natural Sand on Concrete Properties - Al-Barbar, Mohammed Mansour; Agwila, Abdullah Ali; Al-Amami, Bouzid Mustafa; Ashmila, Imran Salem (The annual Scientific Conference for Under and Postgraduate Students at the University., 2024)
Many quarries are spread randomly and irregularly; in the city of Zliten, the environmental impacts resulting from this sector have increased, which includes many negative aspects that harm the environment, people, and many Fields. From this standpoint, we resorted in this study to the possibility of benefiting from rock crushing waste in quarries and using it as manufactured sand, as a partial substitute for natural sand in concrete mixtures. In this study, concrete mixtures were designed and mixing ratios (3: 1.5: 1) are fixed for cement, fine aggregate, and coarse aggregate, respectively. manufactured sand was used as a partial substitute for fine aggregate (sand) in the manufacture of concrete with replacement ratios (5,10, 25, 50) %, to evaluate the validity where The suitability of using manufactured sand in concrete mixtures was evaluated through a set of tests, such as determining the workability properties, compressive strength and indirect tensile strength of concrete. It was observed in this study that the higher the percentage of manufactured sand in the concrete mixture, the less workability is becoming, as the water/cement ratio in all mixtures was 45%. A reference mixture (X1) was made to compare the results obtained from other mixtures according to the replacement ratios for manufactured sand. According to this study, the slump value ​​of concrete in the reference mix (X1) was 55mm, and the lowest slump value for all mixtures was 25 mm for (Y4) mix when using a 50% replacement ratio of manufactured sand. For the compressive strength at age of 28 days, the highest value for all mixtures was 50.6 MPa when using 50% manufactured sand. For the results of indirect tensile strength at age of 28 days, all values ​​for concrete mixtures were close, and the highest value was 2.53 MPa when using manufactured sand with a 5% replacement ratio. According to this study, manufactured sand can be used as a partial substitute in concrete mixtures.
Keywords: Manufactured Sand; Workability of concrete; Compressive Strength of Concrete; Tensile Strength